PRAKTIK PEDAGANG PASAR TRADISIONAL: Fakta dan Solusi Penerapan Etika Bisnis Islami - Nilam Sari (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2018)
Traditional markets are one of the heart of the economy. Traditional markets are very necessary in supporting national economic growth. The rapid development of modern markets is felt by many parties impacting the existence of traditional markets. Along with this, the facts in the field show a shift in ethics in trade in traditional markets. In Islam, values and ethics in all aspects of human life as a whole are very important, including aspects of business activities. This article will explain the extent to which Islamic business ethics have been applied by traders in the Aceh Besar lambaro market, as well as what efforts should be made so that traders always apply Islamic business ethics in running their businesses. The results of the study found that traders had not fully implemented Islamic business ethics as required. Indicators are always honest on the scale, selling quality goods, do not hide the defects of goods, on average under 50% of traders who answer always carry out the indicators of business ethics. As for other business ethics indicators such as accuracy in promising, patience, friendliness, tithing, prayer services, on average above 50% traders said they could carry out the ethics properly. In order for traders to always be consistent in applying business ethics, awareness of the the trader himself to implement it, the role of the buyer as a consumer who understands his rights and obligations is important in the implementation of Islamic business ethics in the market. The supervisory function of the government also plays an important role in ensuring the implementation of Islamic business ethics of the lambaro market traders. Local governments can form market supervisory institutions that collaborate with market organizations headed by one of the market traders. Supervisory agencies and market organizations will jointly oversee the operations of activities in the Lambaro market, both in terms of cleanliness, security, supply of goods, including ensuring the implementation of business ethics for traders and following up all forms of violations that occur in the market.